Social Media, Applications And Understanding In The Community (Expolatory Study: Social Media Literation In Citizens - Rachmat, Ikbal; Abdurahman; Humaira, Sahira; Nilasari, Irma (International Journal of Psychosocial Rehabilitation, 2020)
Social Media Research, Its Applications and Understanding in the Community (Exploration Study: Social Media Literacy in the Residents of Duri Kepa Village, West Jakarta) aims to get the perspective of the community of Duri Kepa Village, West Jakarta in understanding social media applications, especially in online shopping activities, hoaxes and content that contains elements pornography. This research uses a descriptive qualitative approach. Sampling with Nonprobability Sampling technique, with Purposive Sampling, through interviews with several residents of RT 016 RW 007, Duri Kepa, West Jakarta. The results of this study illustrate that in the midst of the development of information and communication technology in the era of information disclosure with the ease of accessing cyberspace at this time, in general, residents of RT 016 RW 007 Duri Kepa Village, West Jakarta already know and do not easily believe in news / short messages that accepted online media, supervising their family members to be more vigilant and careful in conducting activities in cyberspace in order to avoid cyber crime especially social media as an online communication platform, so social media literacy activities are an important part of citizens so as to be able to ward off various forms of reporting that is not true whereabouts / hoaxes, fraud from shopping sites/fictitious online shopping sites to spread pornographic sites to hang out on social media.